1998
DOI: 10.1046/j.1365-2125.1998.00655.x
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacokinetic and pharmacodynamic study of intravenous vs oral artesunate in uncomplicated falciparum malaria

Abstract: Aims To obtain comprehensive pharmacokinetic and pharmacodynamic data for artesunate (ARTS) and its active metabolite dihydroartemisinin (DHA) following i.v. and oral administration of ARTS to patients with acute, uncomplicated falciparum malaria. Methods Twenty-six Vietnamese patients with falciparum malaria were randomized to receive either i.v. ARTS (120 mg; group 1) or oral ARTS (100 mg; group 2), with the alternative preparation given 8 h later in an open crossover design. Mefloquine (750 mg) was administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
119
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(145 citation statements)
references
References 32 publications
20
119
4
Order By: Relevance
“…The most reasonable choice seems to be the use of dihydroartemisinin for in vitro assays since this derivative is relatively stable and all currently used artemisinin derivatives and those that are under advanced phases of development are rapidly transformed into dihydroartemisinin in humans. [14][15][16][17] The significant positive correlation between the in vitro responses to chloroquine and monodesethylamodiaquine or quinine and between the response to mefloquine and halofantrine is in agreement with in vivo resistance to amodiaquine, quinine, and halofantrine observed in Southeast Asia where a high level of resistance to chloroquine and mefloquine has emerged. 41,42 Cross-resistance between pyrimethamine and cycloguanil has also been observed in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The most reasonable choice seems to be the use of dihydroartemisinin for in vitro assays since this derivative is relatively stable and all currently used artemisinin derivatives and those that are under advanced phases of development are rapidly transformed into dihydroartemisinin in humans. [14][15][16][17] The significant positive correlation between the in vitro responses to chloroquine and monodesethylamodiaquine or quinine and between the response to mefloquine and halofantrine is in agreement with in vivo resistance to amodiaquine, quinine, and halofantrine observed in Southeast Asia where a high level of resistance to chloroquine and mefloquine has emerged. 41,42 Cross-resistance between pyrimethamine and cycloguanil has also been observed in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 64%
“…[10][11][12][13] Although pharmacokinetic data are incomplete, it has been established that all currently available artemisinin derivatives are metabolized rapidly to dihydroartemisinin, the biologically active main human metabolite. [14][15][16][17] In the case of sodium artesunate, the aqueous solution that is reconstituted by dissolving the anhydrous powder of the drug in 5% dextrose solution just before parenteral administration is known to hydrolyze the compound rapidly into dihydroartemisinin. 18 Initial in vitro studies on laboratory-adapted clones of P. falciparum have shown that dihydroartemisinin is more active than the other artemisinin derivatives.…”
mentioning
confidence: 99%
“…Assay of DHA in CSF was done by gas chromatography-mass spectrometry (15). For plasma assays, the relative standard deviations [RSDs] have been published (2,3), while RSDs between runs were Յ11% over the ranges of artesunate and DHA concentrations found in our patients. The limits of detection were 80 nmol/liter for artesunate and 70 nmol/liter for DHA.…”
mentioning
confidence: 99%
“…This concentration, 0.11 Ϯ 0.02 mol/liter (mean Ϯ standard error of the mean; n ϭ 12), is only 10% of that required to inhibit neurite outgrowth in vitro, 1 mol/liter (21). We did not sample beyond 120 min, as concentrations of DHA in plasma after intravenous administration of artesunate are very low at this time (3,7). By contrast, the CSF concentration-time profile suggests that DHA could persist in CSF beyond 120 min.…”
mentioning
confidence: 99%
“…Many studies have investigated pharmacokinetic modeling for AS and DHA: non-, one-, and two-compartment and parent-metabolite simultaneous modeling [23][24][25][26]. The parent-metabolite (AS-DHA) simultaneous modeling was also applied in this study, but failed to fit the data or stabilize the parameters because the conversion of AS to DHA after its intravenous administration was too fast to accurately evaluate the conversion rate, namely the absorption rate constant (ka) of DHA; therefore, the pharmacokinetic analysis of AS and DHA were performed separately.…”
Section: Discussionmentioning
confidence: 99%